Literature and medicine: evaluating a special study module using the nominal group technique. - Lancaster, T; Hart, R; Gardner, S (2002)
OBJECTIVES: To evaluate a special study module in literature and medicine that aimed for clinical relevance. METHODS: We organised a 4-week course around themes such as empathy, death and dying, disability, madness and creativity, addiction, domestic violence, ethical dilemmas, doctor/patient communication, doctors' emotions and end of life decisions. We used a diversity of texts and genres to address these themes. We explicitly encouraged the students to engage with both content and form when studying literature. To evaluate the course we used a nominal group technique. Students identified a range of items in response to open questions about the content and methods of the course. After clarifying and reducing the items generated, they ranked them in order of importance. To investigate perceived clinical relevance, we grouped the individual items into broader themes using a previously suggested taxonomy of clinical relevance. RESULTS: The students attached the highest importance to the insights gained into patients and their experience of illness. These encompassed aspects of understanding, knowledge and empathy. They also perceived that they had improved clinically relevant skills including communication, analysis, presentation, writing and ethical reasoning. The remaining items were more broadly concerned with themes of personal growth, development and pleasure. CONCLUSIONS: There are many objectives in studying literature. We focussed on designing a special study module that explicitly emphasised clinical relevance. Our evaluation shows that students identified clinically relevant improvements in knowledge, skills and attitudes from having taken the course.